Keuntungan dan Kerugian Kewirausahaan - Alya Fitriani; Depin Depin; Hafiz Nur (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
Entrepreneurship has many benefits for individuals and society. Entrepreneurship also has several advantages and disadvantages, the following are some of the advantages of entrepreneurship, the advantages of being your own business, gaining satisfaction and social recognition, not being under the orders of others. Apart from that, entrepreneurship can also be a source of employment, build character and positive attitudes, increase experience and learning. However, entrepreneurship also has several disadvantages, such as personal sacrifice, burden of responsibility, small profit margins and the possibility of failure. So in this journal we will discuss further the advantages and disadvantages of entrepreneurship and how people can improve the quality of their lives through entrepreneurship.